Web-Based Information System Design for BUMDes Sakinah in Sialang Panjang Village - Hasan Arya Sandy; Ilyas Ilyas; Abdul Muni (Journal of Computer Science and Informatics Engineering, 2026)
Village-Owned Enterprises (BUMDes) play an important role in improving the rural economy. However, administrative management, business data processing, document archiving, and information dissemination at BUMDes Sakinah in Sialang Panjang Village were still carried out manually, resulting in inefficiency, a high risk of data loss, and delays in providing accurate information. This condition indicates a gap in the utilization of information technology to support integrated BUMDes management. This study aimed to design a web-based information system for BUMDes Sakinah as a solution to these problems. A qualitative research method was employed, with data collected through observation, interviews, and documentation. The system was developed using the System Development Life Cycle (SDLC), consisting of planning, analysis, design, implementation, testing, and maintenance stages. The results show that the proposed system successfully integrates business data management, digital document archiving, and information services into a single web-based platform, thereby improving effectiveness, efficiency, data security, and accessibility of information. Practically, the system supports better administrative management and service quality, while academically it contributes to the implementation of web-based information systems for Village-Owned Enterprises. In conclusion, the developed system has proven to enhance the effectiveness, transparency, and accountability of BUMDes management